Progress on High Voltage PEO-based Polymer Solid Electrolytes in Lithium Batteries - Hou, Wenhui; Ou, Yu; Liu, Kai (Chemical research in Chinese universities, 2022)
Polymer electrolytes have attracted great interest for next-generation lithium-based batteries on account of safety and high energy density. In this review, we assess recent progress on the design of poly(ethylene oxide)(PEO)-based solid polymer electrolytes in high voltage lithium batteries and identify possible side reactions between PEO-based electrolytes and existing cathodes. We provide an overview of the ways to enhance high voltage resistance of PEO-based electrolytes. Those include components blend, molecular design and interface modification. With these efforts, we want to present new insights into rational design of PEO-based electrolytes to develop solid-state lithium batteries for advanced performance.